Design and implementation of a magic mirror using Kinect - Monir, Md. Moniruzzaman; Siddique, Md. Nafis Hasan; Tanni, Afsana Pervin; Hashem, Md. Nahyan Ebn (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.